Base-mediated ketenimine formation from N-sulfonylthioimidates for the synthesis of 5-amino-1-vinyl/aryl-1, 2, 3-triazoles. Issue 10 (12th January 2023) - Chen, Wan-Yu; Lin, Wei-Han; Kuo, Chia-Jou; Liang, Chien-Fu
Abstract : N -Sulfonylthioimidate was converted to ketenimine under basic conditions. The reaction with vinyl/aryl azides was induced to cause dipolar cycloaddition to form 5-amino-1-vinyl/aryl-1, 2, 3-triazoles. Abstract : N -Sulfonylthioimidate was converted to ketenimine under basic conditions. The reaction with vinyl/aryl azides was induced to cause dipolar cycloaddition to form 5-amino-1-vinyl/aryl-1, 2, 3-triazoles. The advantages of this method are high efficiency, structural diversity of products favorable yields and applicability to gram-scale operations.